Capsular Serotyping of Streptococcus pneumoniae Using the Quellung Reaction - Habib, Maha (MyJove Corporation, 2014)
There are over 90 different capsular serotypes of Streptococcus pneumoniae (the pneumococcus). As well as being a tool for understanding pneumococcal epidemiology, capsular serotyping can provide useful information for vaccine efficacy and impact studies. The Quellung reaction is the gold standard method for pneumococcal capsular serotyping. The method involves testing a pneumococcal cell suspension with pooled and specific antisera directed against the capsular polysaccharide. The antigen-antibody reactions are observed microscopically. The protocol has three main steps: 1) preparation of a bacterial cell suspension, 2) mixing of cells and antisera on a glass slide, and 3) reading the Quellung reaction using a microscope. The Quellung reaction is reasonably simple to perform and can be applied wherever a suitable microscope and antisera are available.